A study on heat and mass transfer through vegetated porous concrete for environmental control. (15th September 2022) - Rahman, Md Sazan; MacPherson, Sarah; Akbarzadeh, Abdolhamid; Guerini, Alexandre; Chapelat, Julien; Lefsrud, Mark
Abstract: Porous concrete is an alternative building material that allows for air and water circulation, while exhibiting adequate compressive strength suitable for infrastructure. In this study, a novel vegetation-covered bio-receptive porous concrete prototype was tested for its heating, ventilation, and air conditioning (HVAC) unit control capacity using water as the energy transferring medium. Energy-transferring coils allowing waterflow were placed evenly in a cylindrical-shaped porous concrete cast that upon hardening, was sown with ryegrass ( Lolium perenne ) and hydroponically grown for 60 days. The vegetation-covered porous concrete cylinder was connected with air duct followed by three centrifugal fans while performing heating, cooling, humidification, and dehumidification tests to determine heat and mass transfer capacity. Maximum possible heating and cooling heat transfer were 238.8 ± 4.1 W and −116.65 ± 7.99 W, respectively. Maximum possible humidification and dehumidification mass transfer was 3.42 ± 0.34 g kg −1, and -9.04 ± 0.9 g kg −1, respectively. Vegetated porous concrete showed passive dehumidification of −4.57 ± 0.22 g kg −1 without requiring any external energy. The zero-energy dehumidification capacity of vegetated porous concrete supports the tendency of a green biomass layer in neutralizing the extreme air properties. Results illustrate a new application in green infrastructure for this permeable building material by demonstrating the capacity of vegetated porous concrete in HVAC control, showing potential in green wall applications as a environmentally controlled plant growing-substrate for hydroponics. Highlights: Porous concrete (25–30% void) is readily permeable to air and water. Porous concrete may be used as a plant-growing substrate. Heat (239 W) and mass (3.42 g kg −1 ) control is possible through a growing substrate. A porous concrete green wall provides HVAC with an energy transfer of 36.82 kJ kg −1 .